New developments of the in-source spectroscopy method at RILIS/ISOLDE - Marsh, Bruce; Atanasov, Dinko; Fink, Daniel; Kreim, Susanne (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
At the CERN ISOLDE facility, long isotope chains of many elements are produced by proton-induced reactions in target materials such as uranium carbide. The Resonance Ionization Laser Ion Source (RILIS) is an efficient and selective means of ionizing the reaction products to produce an ion beam of a chosen isotope. Coupling the RILIS with modern ion detection techniques enables highly sensitive studies of nuclear properties (spins, electromagnetic moments and charge radii) along an isotope chain, provided that the isotope shifts and hyperfine structure splitting of the atomic transitions can be resolved. At ISOLDE the campaign to measure the systematics of isotopes in the lead region (Pb, Bi, Tl and Po) has been extended to include the gold and astatine isotope chains. Several developments were specifically required for the feasibility of the most recent measurements: new ionization schemes (Po, At); a remote controlled narrow line-width mode of operation for the RILIS Ti:sapphire laser (At, Au, Po); isobar free ionization using the Laser Ion Source Trap, LIST (Po); isobar selective particle identification using the multi-reflection time-of-flight mass separator (MR-ToF MS) of ISOLTRAP (Au, At). These are summarized as part of an overview of the current status of the in-source resonance ionization spectroscopy setup at ISOLDE.
Gesehen am 23.06.2021